2014
DOI: 10.1007/s00216-014-8040-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of exosome separation techniques and characterization of B16-F10 mouse melanoma exosomes with AF4-UV-MALS-DLS-TEM

Abstract: Exosomes participate in cancer metastasis, but studying them presents unique challenges as a result of their small size and purification difficulties. Asymmetrical field flow fractionation with in-line ultraviolet absorbance, dynamic light scattering, and multi-angle light scattering was applied to the size separation and characterization of non-labeled B16-F10 exosomes from an aggressive mouse melanoma cell culture line. Fractions were collected and further analyzed using batch mode dynamic light scattering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 49 publications
2
100
1
1
Order By: Relevance
“…It contradicts common claims that exosomes have a Bcup shape^ [23] (as illustrated in Fig. 5d) reported on the basis of electron microscopy imaging of desiccated samples [12,[45][46][47] and AFM of both hydrated and desiccated exosomes [48][49][50]. Our finding is supported by prior cryo-TEM results that report round morphology [51] of exosomes released by hepatocytes, spheroid shape [52] of human mesenchymal stem cell exosomes, and naturally spherical [53] exosomes secreted by prion-infected cells.…”
Section: Exosomes Are Spherical Bioparticlescontrasting
confidence: 62%
“…It contradicts common claims that exosomes have a Bcup shape^ [23] (as illustrated in Fig. 5d) reported on the basis of electron microscopy imaging of desiccated samples [12,[45][46][47] and AFM of both hydrated and desiccated exosomes [48][49][50]. Our finding is supported by prior cryo-TEM results that report round morphology [51] of exosomes released by hepatocytes, spheroid shape [52] of human mesenchymal stem cell exosomes, and naturally spherical [53] exosomes secreted by prion-infected cells.…”
Section: Exosomes Are Spherical Bioparticlescontrasting
confidence: 62%
“…PATL1 and PATL2 both bind phosphoinositides and are thought to mediate vesicle transport and/or fusion (Petersen et al, 2014). PATL1 has been localized to the cell plate in dividing cells but also associates with PLASMODESMATA-LOCATED PROTEIN1 (PDLP1) during downy mildew infection and may colocalize with PDLP1 at the extrahaustorial membrane (Caillaud et al, 2014).…”
Section: Protein Content Of Plant Evsmentioning
confidence: 99%
“…For example, Momen-Heravi et al reported that culturing B lymphocytes in the presence of IL-4 and CD40 increased exosome production by over 200-fold [25]. Large numbers of exosomes might then be isolated from culture or biological fluids using advanced microfluidic isolation strategies [39]. Other potential options to scale up exosomal nanocarrier production include the use of bovine milk-derived [40] or plant-derived [14,15] exosomes following biocompatibility testing.…”
Section: Future Perspectivementioning
confidence: 99%